KARAKTERISTIK NILAI GIZI DAN ORGANOLEPTIK KUE BARUASA DARI BERBAGAI FORMULASI TEPUNG KOMPOSIT : STUDI KEPUSTAKAAN - Hasmira, Hasmira; Wahyuni, Sri; Faradilla, RH Fitri (Jurnal Sains dan Teknologi Pangan, 2022)
ABSTRACTThis review aims to investigate the characteristics of the nutritional and organoleptic values of the baruasa cake formulation of various types of local food composite flour. Composite flour is flour derived from tubers, beans, or cereals with or without flour or wheat and is used as a raw material for food preparations. The formulation process of various composite flour is carried out to improve the characteristics of the new cake produced. The results of the review show that the characteristics of the nutritional value of baruasa cake products are influenced by different formulations and other mixed food additives from various composite flours. The product has met the Indonesian National Standard (SNI) based on the characteristics of nutritional value. The results of the organoleptic assessment generally showed that the new cake products made from composite flour formulations were favored by the panelists.Keywords: Nutritional value, baruasa, composite flour.ABSTRAKReview ini bertujuan untuk mengidentifikasi karakteristik nilai gizi dan organoleptik kue baruasa formulasi berbagai jenis tepung komposit pangan lokal. Tepung komposit adalah tepung yang berasal dari umbi-umbian, kacang-kacangan, atau sereal dengan atau tanpa tepung terigu atau gandum dan digunakan sebagai bahan baku olahan pangan. Proses formulasi berbagai tepung kompsit dilakukan untuk untuk memperbaiki karakteristik kue baruasa yang dihasilkan. Hasil review menunjukkan bahwa karakteristik nilai gizi produk kue baruasa dipengaruhi oleh formulasi yang berbeda dan bahan tambahan pangan campuran lainnya dari berbagai tepung komposit. Produk tersebut telah memenuhi Standar Nasional Indonesia (SNI) berdasarkan karakteristik nilai gizi. Hasil penilaian organoleptik secara umum menunjukkan produk kue baruasa yang dibuat dari bahan baku formulasi tepung komposit disukai oleh panelis.Kata kunci: Nilai gizi, baruasa, tepung komposit.